2020
DOI: 10.3389/fped.2020.00404
|View full text |Cite
|
Sign up to set email alerts
|

A Giant Childhood Mesenteric Lipoblastoma With Extensive Maturation

Abstract: Abdominal lipoblastomas are uncommon soft tissue tumors in children and rarely arise from the mesentery. Due to intraabdominal location and slow growth, these masses can go unnoticed for long periods of time and often found on surgical exploration. We present a case of a 12-year-old male with years of abdominal distension accompanied by new onset early satiety that was found to have an intra-abdominal mass. He underwent an exploratory laparotomy revealing a large 33 x 27 x 15 cm rubbery mesenteric mass displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The tumor can be completely resected under laparoscopy.When a patient is admitted to the hospital due to torsion of the greater omentum, laparoscopic exploration can be performed in the emergency department, both laparoscopic tumor resection and the greater omentum resection can be performed at the same time. According to previous reports in the literature, the recurrence rate after resection is <5%, mainly due to incomplete resection (17).…”
Section: Discussionmentioning
confidence: 91%
“…The tumor can be completely resected under laparoscopy.When a patient is admitted to the hospital due to torsion of the greater omentum, laparoscopic exploration can be performed in the emergency department, both laparoscopic tumor resection and the greater omentum resection can be performed at the same time. According to previous reports in the literature, the recurrence rate after resection is <5%, mainly due to incomplete resection (17).…”
Section: Discussionmentioning
confidence: 91%
“…Some studiesrevealed extremities are the most common site (61%) and this is followed by trunk (15%), abdomen (14%) and in head and neck region (11%) whereas, other studies demonstrated a preponderance of the tumor site is in the trunk (44%-48%) and these may also arise in the spine, mediastinum, lungs, trunk, mesentery, peritoneal cavity, retro peritoneum and inguinal canal 1,8,3,9,10,11,12,13,14 .Among them abdominal lipoblastomas which are uncommon comprising around 7% of all reported lipoblastomas and most commonly found in the retroperitoneum. Only less than 15 reported cases abdominal lipoblastoma were noticed to arise in the mesentery 15,16 .We report such a rare childhood soft tissue tumor that was noticed in the abdomen of a 2 years female child presented with huge abdominal distension along with intermittent abdominal pain. Exploratory laparotomy revealed a giant intraabdominal mesenteric mass and both histopathological and immunohistochemistry jointly reported this as a case of lipoblastoma.…”
Section: Introductionmentioning
confidence: 83%
“…A review included 263 cases (13 case series) of lipoblastoma with a median age at presentation of 22.6 months [ 10 ], and a 1.7:1 male-to-female ratio, which indicates a slight male predominance [ 8 , 10 ]. Abdominal lipoblastomas are rare; around 7% of all lipoblastomas and the majority of them develop retroperitoneally [ 6 , 11 , 12 ]. Lipoblastoma occurs in 80% of cases, whereas lipoblastomatosis occurs in 20% of cases [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipoblastoma occurs in 80% of cases, whereas lipoblastomatosis occurs in 20% of cases [ 13 ]. Lipoblastoma and lipoblastomatosis are benign and do not have a risk to metastasize or undergo malignant transformation [ 1 , 3 , 4 , 6 , 13 ], the natural history of an unresected lipoblastoma may be maturing into a lipoma [ 4 , 6 , 11 ]. The recurrence rate reported ranges from 13% to 46% in seven case series [ 8 ].…”
Section: Discussionmentioning
confidence: 99%